Interferon-α2 Auto-antibodies in Convalescent Plasma Therapy for COVID-19 - Raadsen, Matthijs P.; Gharbharan, Arvind; Jordans, Carlijn C. E.; Mykytyn, Anna Z.; Lamers, Mart M.; van den Doel, Petra B.; Endeman, Henrik; van den Akker, Johannes P. C.; GeurtsvanKessel, Corine H.; Koopmans, Marion P. G.; Rokx, Casper; Goeijenbier, Marco; et al. (Journal of clinical immunology, 2022)
Purpose To study the effect of interferon-α2 auto-antibodies (IFN-α2 Abs) on clinical and virological outcomes in critically ill COVID-19 patients and the risk of IFN-α2 Abs transfer during convalescent plasma treatment. Methods Sera from healthy controls, cases of COVID-19, and other respiratory illness were tested for IFN-α2 Abs by ELISA and a pseudo virus–based neutralization assay. The effects of disease severity, sex, and age on the risk of having neutralizing IFN-α2 Abs were determined. Longitudinal analyses were performed to determine association between IFN-α2 Abs and survival and viral load and whether serum IFN-α2 Abs appeared after convalescent plasma transfusion. Results IFN-α2 neutralizing sera were found only in COVID-19 patients, with proportions increasing with disease severity and age. In the acute stage of COVID-19, all sera from patients with ELISA-detected IFN-α2 Abs (13/164, 7.9%) neutralized levels of IFN-α2 exceeding physiological concentrations found in human plasma and this was associated with delayed viral clearance. Convalescent plasma donors that were anti-IFN-α2 ELISA positive (3/118, 2.5%) did not neutralize the same levels of IFN-α2. Neutralizing serum IFN-α2 Abs were associated with delayed viral clearance from the respiratory tract. Conclusions IFN-α2 Abs were detected by ELISA and neutralization assay in COVID-19 patients, but not in ICU patients with other respiratory illnesses. The presence of neutralizing IFN-α2 Abs in critically ill COVID-19 is associated with delayed viral clearance. IFN-α2 Abs in COVID-19 convalescent plasma donors were not neutralizing in the conditions tested.